Synthesis and In Vitro Evaluation of Novel Nortropane Derivatives as Potential Radiotracers for Muscarinic M2 Receptors. (13th June 2011) - Knol, Remco J. J.; van den Bos, Jan C.; Janssen, Anton G. M.; de Bruin, Kora; van Eck-Smit, Berthe L. F.; Booij, Jan
Abstract : Disturbances of the cerebral cholinergic neurotransmitter system are present in neurodegenerative disorders. SPECT or PET imaging, using radiotracers that selectively target muscarinic receptor subtypes, may be of value for in vivo evaluation of such conditions. 6 β -acetoxynortropane, a potent muscarinic M2 receptor agonist, has previously demonstrated nanomolar affinity and high selectivity for this receptor. Based on this compound we synthesized four nortropane derivatives that are potentially suitable for SPECT imaging of the M2 receptor. 6 β -acetoxynortropane and the novel derivatives were tested in vitro for affinity to the muscarinic M1−3 receptors. The original 6 β -acetoxynortropane displayed high affinity (K i = 70 – 90  nM) to M2 receptors and showed good selectivity ratios to the M1 (65-fold ratio) and the M3 (70-fold ratio) receptors. All new derivatives showed reduced affinity to the M2 subtype and loss of subtype selectivity. It is therefore concluded that the newly synthesized derivatives are not suitable for human SPECT imaging of M2 receptors.